STUDIES ON INDUCTION OF ERYTROCYTE ABNORMALITIES IN CIRRHINUS MRIGALA EXPOSED TO DYEING INDUSTRY EFFLUENT - HARBHAJAN KAUR; ROHIT KALOTRA; GURINDER K WALIA; DIANA HANDA (International Journal of Pharma and Bio Sciences, 2013)
Erythrocyte abnormality test has been used to detect the genotoxic effect of dyeing industry effluent on the fish. The 96h LC50 of effluent against Cirrhinus mrigala was calculated by Finney method and three sublethal concentrations 24.48%, 12.24% and 6.12% were made. Fishes were kept in concentrations and blood was smeared after 24h, 48h, 72h and 96h. Eleven types of erythrocyte abnormalities were observed. Nuclear abnormalities included Nuclear Extrusion (NE), Blebbed (B), Binucleate (BN), Lobed (L), Notched (N) nuclei and cellular abnormalities included Enucleated (EnC), Vacuolated (VC), Deformed (DC), Echinocytic (EC), Spindle shaped (SC) and Apoptotic (AC) Cells. Data was statistically significant at (p<0.05) level of significance. 12.24% and 24.48% concentrations proved to be more toxic. In 6.12% concentration, abnormalities decreased at 96h. Erythrocyte abnormalities indicated that effluent induced clastogenic effects on the erythrocytes of Cirrhinus mrigala and may have similar effects on the human population located around the river and consume fishes.